Relationship of neck disability and fear-avoidance beliefs among bankers. - Shoukat , Faryal; Rajar , Huzaifa Ather; Baig, Nabeel (International Journal of Endorsing Health Science Research, 2022)
Background: Neck Disability (ND) is a global health concern among bankers due to the prolonged computer usage demand of the job. Literature reported neck pain and fear of activity among bankers; however, evidence is scarce regarding the association between them. Therefore this survey aimed to evaluate the relationship between ND and Fear Avoidance Beliefs (FAB) among bankers. Methodology: A cross-sectional survey was conducted on bankers of Karachi, Pakistan, using a convenience sampling technique. Volunteer bankers working for two or more years, and having neck pain for more than three months were enrolled in the study. ND was evaluated using Neck Disability Index (NDI) questionnaire and FAB questionnaire to assess activity fear. Statistical analysis was undertaken using SPSS version 20. Pearson correlation test was used to analyze the association between ND and FAB. P-value <0.05 was considered statistically significant at 95% CI. Results: A total of 100 bankers were included in the study. The Pearson correlation test shows a significant moderate and positive correlation between NDI and FAB among bankers (r=0.61). Conclusion: It was concluded that the bankers suffer from ND and fear of activity performance, and a significant moderate and positive association was found between ND and FAB. Hence, further experimental research related to neck posture, work-station ergonomics, and ND is needed so that the global issue can be resolved and bankers' work performance could be enhanced.